2018
DOI: 10.18689/mjs-1000103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on Laparoscopic Transabdominal Pre-Peritoneal (TAPP) Mesh Repair and Total Extra-Peritoneal (TEP) Repair in Inguinal Hernia

Abstract: Background: Laparoscopic TEP and TAPP are the commonly performed methods of laparoscopic repair of inguinal hernia. Lack of documentation and inadequate follow-up have made the learning curve of TEP and TAPP all the more steep thus delaying the standardization of the procedure. The aim of our study is to compare transabdominal preperitoneal mesh repair and total extra-peritoneal repair of inguinal hernia based on post operative pain, duration of Operation, conversion rates to open method, complications of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Complications like conversion to TAPP and proceed surgery without veress needle decompression among the groups showed statistically significant correlation. Rekhi et al, 15 concluded that higher incidence of post-operative complications is associated with TAPP in comparison to TEP. In contrast Reza et al, 17 reported eTEP procedure is cost effective, has minimum complication with easier learning.…”
Section: Discussionmentioning
confidence: 99%
“…Complications like conversion to TAPP and proceed surgery without veress needle decompression among the groups showed statistically significant correlation. Rekhi et al, 15 concluded that higher incidence of post-operative complications is associated with TAPP in comparison to TEP. In contrast Reza et al, 17 reported eTEP procedure is cost effective, has minimum complication with easier learning.…”
Section: Discussionmentioning
confidence: 99%